Effect of positive deviance approach on promotion of safe disposal of child's feces in rural Tamil Nadu: A community-based quasi-experimental study - S Nancy; S Gayathri; K Mujibur Rahman; P K Govindarajan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Safe disposal of feces is ensured when it is deposited into a toilet, whereas unsafe disposal of child's feces plays a crucial role in disease transmission and environmental pollution. These areas are overlooked by many sanitation promotion interventions. Objective: To determine the effect of positive deviance (PD) approach on safe disposal of child's feces among households who owned a toilet. Materials and Methods: A community-based quasi-experimental study was conducted in the four field practice villages of the Urban Health Training Center, Villupuram, for 18 months. Households who owned a toilet and had a child less than 5 years old were included. After IEC clearance, information was collected from a representative sample of 100 households before intervention and another 100 households after intervention. PD approach was applied for 6 months to promote safe disposal practices in the study villages. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software (version 24). The Chi-square test was used to determine the significance of difference between baseline and endline data. The effect size was calculated to estimate the magnitude of difference between baseline and endline data. Results: Before intervention, only 3% of households disposed the feces into a toilet, while after intervention, almost 38% of households disposed in the toilet (χ2 = 37.39; df = 1; P = 0.001). The effect size (Cramer's V) was found to be 0.43. Conclusion: PD approach demonstrated considerable improvements in safe disposal of child's feces in rural settings. Further, to sustain the behavior change, frequent reinforcement of key messages at frequent intervals needs to be emphasized.